Influence of polymorphisms in candidate genes on carcass and meat quality traits in rabbits. - Hosam M Safaa; Mohamed Ragab; Marwa Ahmed; Belal El-Gammal; Mostafa Helal (PLoS ONE, 2023)
Candidate gene is a powerful approach to study gene-trait association and offers valuable information for genetic improvement using marker-assisted selection. The current work aimed to study the polymorphisms of four single nucleotide polymorphism (SNPs) at located growth hormone (GH), insulin-like growth factor-II (IGF-II), fat mass and obesity-associated (FTO), and insulin receptor substrate-1 (IRS-1) genes, and their association with the carcass, and meat quality traits in rabbits. The SNPs were genotyped using RFLP-PCR in New Zealand White and local Baladi rabbits. The results revealed that the heterozygous genotype was the most frequent in all cases, except for the FTO SNP in LB rabbits. There was a significant effect for GH genotypes on meat lightness after slaughter and hind-part weight. While, IGF-II mutation significantly affected slaughter, hot carcass, commercial carcass, and hind-part weights. The FTO SNP was associated with cooking loss and intramuscular fat weight, and the IRS-1 SNP was significantly associated with drip loss and intramuscular fat. Specific-breed effects were obtained for IGF-II SNP on cooking loss, and for the intramuscular fat. Although the results suggested that these mutations are useful candidate genes for selection, more research for detecting more variants associated with carcass and meat quality traits in rabbits are recommended.